The Spatial Distribution Pattern of Sultan Tombs Within the Buton Palace Fortress Using Geographic Information System (GIS) - Deni Hadi Prasetyo; Sitti Kasmiati; Abdul Alim (Journal of Law, Social Science and Management, 2025)
Background: The Buton Palace Fortress is one of the most significant heritage sites of the Buton Sultanate, with physical remains such as fortifications, cannons, and royal tombs that still reflect the power and socio-political structure of the former sultanate. Objective: This study aims to identify and describe the archaeological remains in the form of sultans’ tombs located within the Buton Palace Fortress complex. Methods: The research employs an environmental approach, utilizing data collection techniques such as field observation, literature review, interviews, and documentation. The data were analyzed using morphological and contextual approaches. Results: The findings reveal that the Buton Palace Fortress continues to symbolize the enduring legacy of the Buton Sultanate, as evidenced by the preserved structures and royal tombs within the fortress. The spatial distribution of the tombs is irregular, influenced by the personal wishes of royal families to be buried within the fortress and by the political context of the respective periods. Conclusion: The sultans' tombs within the Buton Palace Fortress represent a continued symbol of royal authority and sacred values in local culture. The irregular distribution pattern of the tombs reflects social and political factors that influenced burial placement.